Variability in Indonesian Throughflow Upper Hydrology in Response to Precession‐Induced Tropical Climate Processes Over the Past 120 kyr. Issue 8 (13th August 2021) - Zhang, Peng; Xu, Jian; Beil, Sebastian; Holbourn, Ann; Kuhnt, Wolfgang; Li, Tiegang; Xiong, Zhifang; Yan, Hong; Cui, Rui; Liu, Heng; Wu, Hanning
Abstract: The Indonesian Throughflow (ITF), as the sole low‐latitude conduit connecting the Pacific and Indian Oceans, regulates the thermohaline balance between these oceans. Thus, investigating the variability in the ITF and its relationship with the precessional forcing is crucial for understanding the drivers of tropical climate change. Here, we reconstruct the history of the ITF over the past ∼120 kyr based on high‐resolution (∼400 years) δ 18 O and Mg/Ca records of Globigerinoides ruber and Pulleniatina obliquiloculata from core SO217‐18540 retrieved from the Flores Sea upwelling region within the main pathway of the ITF. A comparison of these new records with published paleo‐oceanographic and climatological data from the western tropical Pacific Ocean suggests that annual mean conditions in the Flores Sea were controlled by ITF variability rather than by monsoonal upwelling. Our results further indicate that precessional insolation was a major forcing for the hydrological evolution of the ITF during the past 120 kyr. We suggest that the precessional insolation forcing paced ITF variability by modulating the mean state of El Niño‐Southern Oscillation‐like conditions and latitudinal shifts and/or expansion/contraction of the Intertropical Convergence Zone. Plain Language Summary: The Indonesian Throughflow (ITF) is the only low‐latitude current transporting warmer, fresher water masses from the Pacific to the Indian Ocean, regulating the interocean heat and fresh water budgets. The ITF is strongly influenced by shifts in winds and temperatures across the tropical Pacific Ocean (El Niño‐Southern Oscillation; ENSO) and by variations in the latitudinal position and intensity of the hottest part of the tropical climate belt (Intertropical Convergence Zone; ITCZ). Hence, understanding past ITF variability is highly relevant to constrain projections of future tropical climate change. Here, we present new upper ocean temperature and salinity records spanning the last 120 kyr from core SO217‐18540 retrieved within the main ITF pathway. These records are based on δ 18 O and Mg/Ca analyses of surface and deeper dwelling microscopic zooplankton shells (foraminifera). We found that variations in the ITF intensity and vertical structure were controlled by the ∼20 kyr wobble of the Earth's axis, which affects the distribution of incoming solar radiation. We ascribe this pattern of variability to shifts in the intensity and/or position of the ITCZ and to changes in winds and temperatures over the tropical Pacific Ocean, similar to the modern ENSO but acting on longer timescales in Earth's history. Key Points: The first δ 18 O and Mg/Ca records of G. ruber and P. obliquiloculata that span the last 120 kyr from the main Indonesian Throughflow (ITF) pathway are presented Precessional insolation influenced the thermal evolution of the ITF by modulating the mean state of ENSO‐like conditions Precessional variability in ENSO‐like states coupled to the intensity and latitudinal extent of the Intertropical Convergence Zone forced changes in δ 18 Osw‐c of the ITF